Microtus arvalis ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
175. Common Vole Microtus arvalis French: Campagnol des champs / German: Feldmaus / Spanish: Topillo campesino Other common names: Guernsey Vole (Guernsey |), Orkney Vole (Orkney |) Taxonomy. Mus arvalis Pallas, 1779, “Per omnen [= throughout] Europam & Russiam.” Based on neotype selection, restrict ed by V. M. Malygin and V. N. Yatsenko in 1986 to Pushkin, Leningrad (= St. Petersburg) Oblast, Russia. Microtus arvalis is in subgenus Microtus and arvalis species group. Species now in the subgenus Microtus (i.e. mystacinus, transcaspicus, and ilaeus) and few species in subgenus Alexandromys (e.g. mongolicus) were synonymized with arvalis. Microtus obscurus is most closely related to M. arvalis. The two species share identical diploid number (2n = 46) but differ in morphology of chromosomes: M. obscurus has ten pairs of acrocentric chromosomes and M. arvalis has four pairs. Their distributionsslightly overlap, and they hybridize in a narrow parapatric zone that is up to 10 km wide. Most individuals from ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 351-352, DOI: 10.5281/zenodo.6707142 ...